2017
DOI: 10.1590/1516-3180.2017.0023190317
|View full text |Cite|
|
Sign up to set email alerts
|

Physical activity in Brazil: lessons from ELSA-Brasil. Narrative review

Abstract: CONTEXT AND OBJECTIVE: The Brazilian Longitudinal Study of Adult Health (ELSA-Brasil) was conducted among civil servants at six higher education institutions located in six Brazilian state capitals. The objective of this review was to identify the publications produced within the scope of ELSA-Brasil that analyzed the participants' physical activity. DESIGN AND SETTING: Review study using baseline data from ELSA-Brasil. METHODS: Narrative review of Brazilian studies on physical activity produced using data fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
6
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 12 publications
(4 reference statements)
3
6
0
Order By: Relevance
“…Our study confirms (Tables and ) that the prevalence of low PA levels is higher in women than in men, both worldwide (Althoff et al, ; Guthold et al, ; Hughes, Baker, Kim, & Valdes, ) and in Brazil (da Silva et al, ; Pitanga, Almeida, Queiroz, Aquino, & Matos, ), including among adolescents (Silva et al, ). Women were 6% more physically inactive than men in 2001 and 8% more in 2016.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Our study confirms (Tables and ) that the prevalence of low PA levels is higher in women than in men, both worldwide (Althoff et al, ; Guthold et al, ; Hughes, Baker, Kim, & Valdes, ) and in Brazil (da Silva et al, ; Pitanga, Almeida, Queiroz, Aquino, & Matos, ), including among adolescents (Silva et al, ). Women were 6% more physically inactive than men in 2001 and 8% more in 2016.…”
Section: Discussionsupporting
confidence: 87%
“…Previous studies have shown that individuals with higher education and socioeconomic status from low to middle‐income countries had lower PA levels, probably related with a high grade of work‐related technology and highly sedentary professions (Koyanagi, Stubbs, & Vancampfort, ). Socioeconomic status was also positively associated with leisure‐time PA (da Silva et al, ; Pitanga et al, ) and negatively associated with work‐related PA (da Silva et al, ) in two Brazilian surveys. In a Chinese survey (Du et al, ), total PA was negatively associated with educational level, mainly because of the low occupational PA among Chinese with high academic degrees.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the studies included in the systematic reviews were conducted in developed countries that have socioeconomic and environmental conditions that favor the maintenance of healthier lifestyles [16,20]. In developing countries, such as Brazil, low educational, socioeconomic levels [21] and unfavorable environments contribute to explain the low prevalence of physical activities among the population [22]. Also, Salvo et al [23] ratify the importance of positive environment perception for the practice of leisure-time physical activities among Brazilian adults.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, the frequency of individuals performing regular exercise remains low in developed and developing countries [ 4 , 5 ]. One of the main causes reported worldwide by individuals for physical inactivity is a lack of time to perform an exercise program [ 6 ].…”
Section: Introductionmentioning
confidence: 99%